2021
DOI: 10.1101/2021.09.16.460667
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The landscape of nucleotide diversity inDrosophila melanogasteris shaped by mutation rate variation

Abstract: What shapes the distribution of nucleotide diversity along the genome? Attempts to answer this question have sparked debate about the roles of neutral stochastic processes and natural selection in molecular evolution. However, the mechanisms of evolution do not act in isolation, and integrative models that simultaneously consider the influence of multiple factors on diversity are lacking; without them, confounding factors lurk in the estimates. Here we present a new statistical method that jointly infers the g… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(18 citation statements)
references
References 136 publications
0
18
0
Order By: Relevance
“…Adding other genomic markers besides SNPs will improve full genome approaches, which are currently limited by the observed nucleotide diversity [34,58,54]. We predict that our results pave the way to improve the inference of 1) biological traits or recombination rate through time [14,60], 2) multiple merger events [36], and 3) recombination and mutation rate maps [5,4]. Our method also should help to dissect the effect of evolutionary forces on genomic diversity [32,31], and to improve the simultaneous detection, quantification and dating of selection events [1,8,30].…”
mentioning
confidence: 75%
See 1 more Smart Citation
“…Adding other genomic markers besides SNPs will improve full genome approaches, which are currently limited by the observed nucleotide diversity [34,58,54]. We predict that our results pave the way to improve the inference of 1) biological traits or recombination rate through time [14,60], 2) multiple merger events [36], and 3) recombination and mutation rate maps [5,4]. Our method also should help to dissect the effect of evolutionary forces on genomic diversity [32,31], and to improve the simultaneous detection, quantification and dating of selection events [1,8,30].…”
mentioning
confidence: 75%
“…Despite the power of the SMC, well-known model violations such as variation of recombination and mutation rates along the genome [5,4] or pervasive selection [53,31,30] can compromise the accuracy of demographic and selective inference [24,56]. There are two other important issues that have received less attention in the literature.…”
Section: A) Neutral Model With Two Markers B) Marker 2 Is Not Heritab...mentioning
confidence: 99%
“…Identifying the driving forces shaping patterns of diversity along the genome of non-model organisms and understanding how theoretical models extend to natural systems is a major endeavor in speciation genomics (Comeron 2014; Elyashiv et al 2016; Stankowski et al 2019; Barroso and Dutheil 2021). In this study, we demonstrated that the interplay between recombination and selection had a strong impact on phylogenetic inference and demographic parameters, which are key for distinguishing alternative spatial models of divergence.…”
Section: Discussionmentioning
confidence: 99%
“…However, other genomic processes might be shaping phylogenetic signals across the genome. For instance, levels of polymorphism across the genome could be derived from variation in mutation rate (Besenbacher et al 2019; Jónsson et al 2018; Smith et al 2018; Barroso and Dutheil 2021). Non-crossover gene conversion (Korunes and Noor 2017), where DNA strands break during meiosis and are repaired based on homologous sequences without crossing-over, and crossover events could be mutagenic, leading to higher mutation rates in areas of higher recombination (Arbeithuber et al 2015; Korunes and Noor 2017).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation